2008
DOI: 10.1099/vir.0.2008/001529-0
|View full text |Cite
|
Sign up to set email alerts
|

An infectious cDNA clone of a highly pathogenic porcine reproductive and respiratory syndrome virus variant associated with porcine high fever syndrome

Abstract: Since May 2006, a so-called ‘porcine high fever syndrome’ (PHFS) has spread all over China. The arterivirus porcine reproductive and respiratory syndrome virus (PRRSV) was believed to be the main causative agent, although the involvement of other pathogens was not formally excluded. The genome of a representative Chinese PRRSV strain, named JX143, was sequenced and used to develop infectious cDNA clones, pJX143 and pJX143M, with the latter containing an engineered MluI site that served as a genetic marker. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…In recent years, reverse genetic operation methods have been extensively applied to study the genomic functions of PRRSV (11,21,26,28,31,32,34,43). A new study indicated that the rescued virus from an infectious cDNA clone of a highly pathogenic PRRSV variant was highly virulent for pigs (24). In our study, a viable virus recovered from an infectious cDNA clone of JXwn06 induced typical clinical symp- toms identical to those observed in the field, displaying high pathogenicity for pigs, like the parent virus.…”
Section: Discussionmentioning
confidence: 70%
“…In recent years, reverse genetic operation methods have been extensively applied to study the genomic functions of PRRSV (11,21,26,28,31,32,34,43). A new study indicated that the rescued virus from an infectious cDNA clone of a highly pathogenic PRRSV variant was highly virulent for pigs (24). In our study, a viable virus recovered from an infectious cDNA clone of JXwn06 induced typical clinical symp- toms identical to those observed in the field, displaying high pathogenicity for pigs, like the parent virus.…”
Section: Discussionmentioning
confidence: 70%
“…After 1 h of incubation at 37°C, cells were washed three times with PBS and incubated at 37°C in 3 ml of Eagle's minimal essential medium (EMEM) containing 2% FBS in a CO 2 incubator. At certain time points (12,24,48,72,96, and 120 h) postinfection, supernatants (0.2 ml/well) were collected and frozen at Ϫ70°C till use. The viral titers (50% tissue culture infective dose [TCID 50 ]/ml) were measured in MARC-145 cells and calculated by the Reed and Muench method (34).…”
Section: Methodsmentioning
confidence: 99%
“…PRRSV JXM100 (GenBank accession no. GQ475526) was obtained through 100 serial passages of the highly pathogenic PRRSV JX143 strain (EU708726) in MARC-145 cells (24). The infectious PRRSV cDNA clone pAJXM was constructed from the cell-adapted strain JXM100 (X. Wang, L. Sun, Y. Li, T. Lin, F. Gao, R. Liu, X. Li, H. Yao, G. Tong, Z. Wei, and S. Yuan, unpublished data) and served as the backbone for all GP5 glycosylation site mutations used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several PRRSV stains have been used as parental viruses to construct full-length infectious clones, including FL12, VR2332, P129, CH-1a, Lelystad virus, and the hpPRRSV JXwn06 and JX143 [18,23,24,27,28,30]. Although JXwn06 and JX143 as hpPRRSV were used to construct the infectious clones, the construction of a reverse genetic platform based on the hpPRRSV was still needed in a different strategy for easier screening and testing of new antiviral drugs in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, establishing an infectious viral genomic clone would be extremely useful to investigate the biology of hpPRRSV. Although two similar infectious clones of the hpPRRSV isolates have been constructed and characterized recently, and the 30 discontinuous amino acid deletion was ruled out as being responsible for the high virulence [23,24], there are still many important scientific questions remaining to be answered. Therefore, the establishment of hpPRRSV infectious clones derived from different strains will provide some new tools for future pathogenesis studies.…”
mentioning
confidence: 99%